2017
DOI: 10.1002/ajpa.23196
|View full text |Cite
|
Sign up to set email alerts
|

The relative position of the human fibula to the tibia influences cross‐sectional properties of the tibia

Abstract: The tibia and fibula experience different loads. The relative position of the two bones leads to compensatory differences in their CSG properties, perhaps due to increased resistance to bending in fibulae with greater distances from the tibia. Examinations of tibial CSG properties without considering the fibula limits interpretations about activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Regarding the leg, while the body of evidence on the structural and biomechanical properties on the tibiofibular complex in adults is progressively increasing (Auerbach et al, 2017 ; Marchi & Shaw, 2011 ; Rantalainen et al, 2010 , 2014 ; Tümer et al, 2019 ), scarce information is available for subadult individuals, with analyses focusing mostly on the tibia (Gosman et al, 2013 ; Hubbell et al, 2011 ). The importance of considering leg bones together (and not the tibia alone) to better understand load distribution in the distal segment of the lower limb has been previously stressed in anthropological and biomechanical studies (Funk et al, 2004 , 2007 ; McNeil et al, 2009 ; Scott et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the leg, while the body of evidence on the structural and biomechanical properties on the tibiofibular complex in adults is progressively increasing (Auerbach et al, 2017 ; Marchi & Shaw, 2011 ; Rantalainen et al, 2010 , 2014 ; Tümer et al, 2019 ), scarce information is available for subadult individuals, with analyses focusing mostly on the tibia (Gosman et al, 2013 ; Hubbell et al, 2011 ). The importance of considering leg bones together (and not the tibia alone) to better understand load distribution in the distal segment of the lower limb has been previously stressed in anthropological and biomechanical studies (Funk et al, 2004 , 2007 ; McNeil et al, 2009 ; Scott et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some studies brought attention to the functional role of the fibula in transmitting to the foot a portion of the mechanical load encountered during gait by the leg, which varies between 5% and 19% depending on ankle position (Funk et al, 2004; Goh et al, 1992; Lambert, 1971; Takebe et al, 1984). Moreover, recent research on the diaphyseal CSG properties of the fibula allowed the association of fibular structure to diverse mobility patterns in modern humans (Auerbach et al, 2017; Hagihara & Nara, 2016; Lüscher et al, 2019; Marchi et al, 2011; Marchi & Shaw, 2011; Sparacello et al, 2014), great apes (Marchi, 2005, 2007), and non‐hominoid primates (Marchi, 2015b), with further application in paleoanthropology and the origins of bipedal locomotion (Marchi, 2015a; Marchi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This study would have benefited from including the fibula in the analysis of the lower limb. Recent work has shown that including fibular shape and robusticity provides more information about mobility than the tibia alone (Auerbach et al 2017;Hagihara and Nara 2016;Sparacello et al 2014). The urban Alkmaar sample showed substantially greater variation in cross-sectional properties compared to both rural samples (Table 5).…”
Section: Discussionmentioning
confidence: 97%
“…Based on these results and on the documented relationship between bone curvature and activity level and mobility 13 , we can assume that most of the observed temporal variation in tibial curvature is derived from non-genetic influences. We must also bear in mind the fact that the tibia is part of a complex with the fibula and that studies focusing on the tibia alone may provide an incomplete picture of leg functional anatomy 67,71 . Taking this into consideration, future studies should also address the fibular shape and robusticity and the anatomical position of the fibula relative to the tibia.…”
Section: Discussionmentioning
confidence: 99%